Utilising the linguistic knowledge of the speech community - Wietmarschen, Gretchen (Te Kaharoa, 2012)
Threatened language groups worldwide have experienced language loss due to official language policies of the state, including forced assimilation. A number of these populations are attempting to aid the revitalisation efforts of their traditional languages by implementing mother-tongue medium education revitalisation programmes within the framework of the formal education system. This research examines the use of intergenerational language transfer as an instructional tool within the formal education language revitalisation programmes of Aotearoa New Zealand. Compelling the researcher to pursue this topic is the apparent lack of cross-generational interaction in schools (grandparents/community members involved in the learning process) regardless of the population served, combined with need for fluent speakers of threatened languages to aid in further language revitalisation. Through a predominantly qualitative research approach this research investigates how many language revitalisation programmes within formal education classrooms in Aotearoa/ New Zealand utilise the linguistic knowledge held by the native speaker community, in particular members of the grandparent generation to impart their knowledge and work with the students. It examines how this method is utilised, or if it is not utilised, why this is the case. In addition to the collection of preliminary pedagogical demographic data from schools, interviews with Kaumatua and classroom teachers, and case study observation of classrooms, provide further depth to this research.